Analisis Yuridis Hak Krama Desa Adat Atas Tanah Pekarangan Desa (PKD) Sebagai Tempat Tinggal dan Bisnis Komersil Berdasarkan Peraturan Daerah No 4 Tahun 2019 - Ni Luh Eka Puspita; I Kadek Dony Hartawan; Ni Komang Irma Adi Sukmaningsih (Universitas Pendidikan Ganesha, 2025)
This research aims to legally analyze the rights of Adat Village Krama (customary villagers) over Village Residential Land) converted into commercial residences under Bali Provincial Regulation Number 4 of 2019 concerning Adat Villages in Bali. This study focuses on two aspects: the legal status and limitations of Krama rights over PKD land according to Regulation Number 4 of 2019, and the validity as well as the legal implications of utilizing such communal land for commercial residences. This study is a normative legal research employing a statute approach and a conceptual approach. The results of this study show that there is a vague norm in Article 62 paragraph (2) letter b of Regulation Number 4 of 2019, specifically within the phrase